1 vote

Best answer

According to the question, $\frac{3+x}{4+x} = \frac{15-x}{17-x}$

$\Rightarrow (3+x)(17-x) = (4+x)(15-x)$

$\Rightarrow \require{cancel} 51-3x + 17x – {\color{Red}{\cancel{x^{2}}}} = 60 + 15x-4x – {\color{Red}{\cancel{x^{2}}}}$

$\Rightarrow 14x-11x = 60-51$

$\Rightarrow 3x = 9$

$\Rightarrow {\color{Blue}{\boxed{x = 3}}}$

Correct Answer $:\text{C}$

$\Rightarrow (3+x)(17-x) = (4+x)(15-x)$

$\Rightarrow \require{cancel} 51-3x + 17x – {\color{Red}{\cancel{x^{2}}}} = 60 + 15x-4x – {\color{Red}{\cancel{x^{2}}}}$

$\Rightarrow 14x-11x = 60-51$

$\Rightarrow 3x = 9$

$\Rightarrow {\color{Blue}{\boxed{x = 3}}}$

Correct Answer $:\text{C}$